2021
DOI: 10.15740/has/ijas/17.2/216-219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spacing and different seed rates on growth, yield and economics of linseed under irrigation

Abstract: Row spacing and seed rate are management practices that affect flax seed yield. Hence to find out the optimum quantity of seed rate and spacing for higher production in irrigated linseed, the present experiment was conducted under AICRP on Linseed, College of Agriculture, Nagpur during the Rabi Season of 2019-20. The Experiment was laid out in Factorial Randomized Block Design with three replications in which Factor A consist of two spacing i.e. T1 - 30 cm and T2 - 45 cm and Factor B includes four seed rate S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Depending on the objective of production, the plant height could be used to modify the seed/straw ratio. Researchers discovered that increasing plant density increased plant height, seed yield, and straw yield [42,45]. During the present study, the plant density showed a very significant positive correlation with the straw yield per decare, seed and fiber yield, and significant correlation with the plant height (Table 4).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Depending on the objective of production, the plant height could be used to modify the seed/straw ratio. Researchers discovered that increasing plant density increased plant height, seed yield, and straw yield [42,45]. During the present study, the plant density showed a very significant positive correlation with the straw yield per decare, seed and fiber yield, and significant correlation with the plant height (Table 4).…”
Section: Discussionsupporting
confidence: 57%
“…It means that a small number of plants cultivated in an unit area can result in acquiring all nutrient, sunshine, and irrigation water requirements, which positively impacts plant growth due to less competition for resources among plants. Some researchers [12,36,37,45,47,48] reported, that long fiber flax production is profitable due to fiber tenacity and fiber elasticity, which renders high fiber quality. Furthermore, they discovered that the yield of straw, fibre, and seed rose with the rise of plant density to a specified level in per unit area, with the maximum yields obtained.…”
Section: Discussionmentioning
confidence: 99%